Horacio de la Costa, Foreign missionaries, and the quest for Filipinization the church in the age of decolonization - Aguilar, Filomeno V., Jr; Sy, Nicholas (Philippine studies : historical and ethnographic viewpoints, 2017)
"Fr. Horacio de la Costa became the first Filipino Superior of the Jesuit Province in the Philippines (1964-1970) at a time when the Filipinization of religious orders was intensely contested. As a young priest, De la Costa sought the training of more Filipino priests so that the Catholic Church would "take root" in the country. Filipinization, however, entailed two further questions: Filipino assumption of leadership positions and the role of foreign questions: Filipino assumption of leadership positions and the role of foreign missionaries. This article examines how De la Costa's approaches to these issues shifted when he became provincial and as the crisis in Philippine society deepened, revealing the intertwining of national and church history."